Coated metal hydrides for stationary energy storage applications - Mistry, Priyen C. (2016)
This thesis explores suitable materials for energy stores for stationary applications, specifically a prototype hydrogen store, domestic thermal store operating between 25-100 C and a moderate thermal store for a concentrated solar power (CSP) plant operating at 400 C. The approach incorporated a unique coating technique to deliver prototype hydrogen and thermal storage media, where the coating could offer commercial advantages, for example, in the form of hydride activation and enhanced kinetics during successive cycling.